Produksi Bioetanol Dari Bungkil Inti Sawit Dengan Proses Fermentasi - Nur Irfana Mardiyah; Silvia Reni Yenti; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Indonesia is a country with a growing human population, causing the need of energy also increases. Bioethanol has been widely used in transportation as a fuel that is increasingly reduced. Palm kernel expeller has a high enough potential to be developed into an alternative energy source, namely bioethanol because of its lignocellulosic content. The purpose of this study was to determine the composition of yeast in the fermentation process, and determine the optimal processing time for the formation of bioethanol in the Hydrolysis and Separate Fermentation (SHF) method. The stages in this study were the hydrolysis of palm kernel expeller using H2SO4 3M for 5 hours at 100 oC. The fermentation process is carried out with variations in time for 24 hours, 48 hours, 72 hours, 96 hours and 120 hours. The fermentation process is carried out with variations composition of yeast for 4 g/L, 6 g/L, dan 8 g/L. The results showed that in the fermentation using a sugar concentration of 22,11 g/L, obtained an optimal fermentation in 2,5 % (v/v) or 19,73 g/L at 6 g/L composition of yeast and 96 hours time on fermentation. The greater the concentration of Saccharomyces cerevisiae and the longer fermentation time, the more bioethanol is obtained. Keywords: Bioethanol, fermentation, palm kernel expeller, Saccharomyces cerevisiae,.